Development of a novel sequence based real-time PCR assay for specific and sensitive detection of Burkholderia pseudomallei in clinical and environmental matrices - Pranjal Kumar Yadav; Suchetna Singh; Moumita Paul; Sanjay Kumar; S. Ponmariappan; Duraipandian Thavaselvam (BMC, 2024)
Abstract Background Melioidosis, caused by the category B biothreat agent Burkholderia pseudomallei, is a disease with a high mortality rate and requires an immediate culture-independent diagnosis for effective disease management. In this study, we developed a highly sensitive qPCR assay for specific detection of Burkholderia pseudomallei and melioidosis disease diagnosis based on a novel target sequence. Methods An extensive in-silico analysis was done to identify a novel and highly conserved sequence for developing a qPCR assay. The specificity of the developed assay was analyzed with 65 different bacterial cultures, and the analytical sensitivity of the assay was determined with the purified genomic DNA of B. pseudomallei. The applicability of the assay for B. pseudomallei detection in clinical and environmental matrices was evaluated by spiking B. pseudomallei cells in the blood, urine, soil, and water along with suitable internal controls. Results A novel 85-nucleotide-long sequence was identified using in-silico tools and employed for the development of the highly sensitive and specific quantitative real-time PCR assay S664. The assay S664 was found to be highly specific when evaluated with 65 different bacterial cultures related and non-related to B. pseudomallei. The assay was found to be highly sensitive, with a detection limit of 3 B. pseudomallei genome equivalent copies per qPCR reaction. The detection limit in clinical matrices was found to be 5 × 102 CFU/mL for both human blood and urine. In environmental matrices, the detection limit was found to be 5 × 101 CFU/mL of river water and 2 × 103 CFU/gm of paddy field soil. Conclusions The findings of the present study suggest that the developed assay S664 along with suitable internal controls has a huge diagnostic potential and can be successfully employed for specific, sensitive, and rapid molecular detection of B. pseudomallei in various clinical and environmental matrices.